Consequences of cyberbullying behaviour in working life: The mediating roles of social support and social organisational climate. Issue 5 (2nd October 2017) - Muhonen, Tuija; Jönsson, Sandra; Bäckström, Martin
Abstract : Purpose: The purpose of this paper is to explore health- and work-related outcomes of cyberbullying behaviour and the potential mediating role of social organisational climate, social support from colleagues and social support from superiors. Design/methodology/approach: Altogether 3, 371 respondents participated in a questionnaire study. Findings: The results of this study indicate that social organisational climate can have a mediating role in the relationship between cyberbullying behaviour and health, well-being, work engagement and intention to quit. Contrary to earlier face-to-face bullying research, the current study showed that cyberbullying behaviour had stronger indirect than direct relationships to health, well-being, work engagement and intention to quit. Practical implications: Communication through digital devices in work life is becoming more prevalent, which in turn increases the risk for cyberbullying behaviour. Organisations need therefore to develop occupational health and safety policies concerning the use of digital communication and social media in order to prevent cyberbullying behaviour and its negative consequences. Originality/value: Cyberbullying behaviour among working adults is a relatively unexplored phenomenon and therefore this study makes valuable contribution to the research field.